GADGET PELANGI UNTUK MEMBANTU KEMANDIRIAN PENYANDANG TUNA NETRA - Muhammad Bagus Arifin; Maqhrisa Rusma; Joni Setiyawan Saputra; Agusta Rakhmat Taufani (SENTIA 2016, 2016)
The new breakthrough in Indonesia in the field of technology of the color sensor tool application gadgets to use output audio and visual related in particular colors. This activity aims to produce a of gadget pelangi that has good quality, safe, and exciting and can help the disabled self-reliance the blind people related to distinguishobjects based on the color them want. Designed so that it can be implemented into a pioneer of the future that can be mass produced. The activities carried out by doing (1) the study of literature, (2) designing hardware and software products (3) experiment on the basis of existing theories, (4) perform modifications based on the results obtained (5) and the consummation product after socialization to disabilities blind people categories with low vision. At the last of the activities of the team of writers producing a of gadget pelangi that works fine.